Use of Radiofrequency Technology in Endonasal Skull Base and Transcranial Procedures - Tish, Shahed; Habboub, Ghaith; Borghei-Razavi, Hamid; Woodard, Troy D.; Sindwani, Raj; Kshettry, Varun R.; Recinos, Pablo F. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Radiofrequency ablation is widely utilized in otorhinolaryngology. It is used for ablation, coagulation and resection, and hemostasis. It causes tissue destruction through a chemical interaction of ions. The potential benefit is to cause less thermal injury to surrounding tissues compared with other coagulative tools. In this article, we present novel uses of radiofrequency ablation in endoscopic endonasal, and transcranial surgery. This is the first study to describe its use in transcranial cases.Design, Setting, and Participants This is a retrospective study of patients between 2016 and 2018 who underwent either endoscopic endonasal or transcranial surgery where radiofrequency ablation was used.Main Outcome Measures We looked at indication for usage, blood loss, postoperative imaging to identify any stroke or edema, and clinical outcomes of these patients.Results The radiofrequency device was used in eight endoscopic endonasal cases and four craniotomies. Four cases were for encephalocele repair and eight were for various intracranial pathologies. In endonasal encephalocele repair, the radiofrequency ablation helped in shrinking the herniated brain while minimizing thermal injury to the surrounding tissue. In tumors resection, the combination of ablation and coagulation effect was particularly effective for highly vascularized tumors. There were no vascular or major neurologic injuries. Postoperative periencephalocele edema was noted in one case.Conclusion Initial experience with radiofrequency ablation showed that it was a safe technique to use in both endonasal skull-base and transcranial procedures. It seemed particularly useful for highly vascularized tumors but a greater experience is needed to further clarify its role in these procedures.
Keywords: coblator; coblation; craniotomy; skull base; radiofrequency ablation